FinTech in the Small Food Business and Its Relation with Open Innovation - Mukhamad Najib; Wita Juwita Ermawati; Farah Fahma; Endri Endri; Dwi Suhartanto (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Small food businesses have difficulty accessing banks for financing. The growth of the sharing economy through financial technology (FinTech) makes it possible for small enterprises to receive access for credit. However, not all small business owners want to receive financing from FinTech companies. This study aims to analyze factors affecting FinTech adoption in small enterprises and its impact on business sustainability. The modified UTAUT 2 model was applied in this study. There were 184 small food business owners participating as respondents. To analyze the causal relationship between variables, Structural Equation Modeling (SEM) was implemented using a Partial Least square (SEM-PLS). The results of the research found that knowledge, safety perceptions, performance expectations, social influence, facilitation conditions and price values affect FinTech adoption by small food business owners. Moreover, FinTech adoption influences small food business sustainability. Several important recommendations for researchers, the FinTech industry and policy makers are formulated.